The unbreakable code eaudiobook - Bertman, Jennifer Chambliss (Book Scavenger, 2017)
A New York Times -Bestseller! Could books hidden through Book Scavenger be linked to an arsonist's web of destruction? Find out in Book 2 of Jennifer Chambliss' The Book Scavenger series. Mr. Quisling is definitely up to something mysterious, and Emily and James are on high alert. First, there's the coded note he drops at a book event. Then they uncover a trail of encrypted messages in Mark Twain-penned books hidden through Book Scavenger. What's most suspicious is that each hidden book triggers a fire. As the sleuthing friends dig deeper, they discover Mr. Quisling has been hunting a legendary historical puzzle: the Unbreakable Code. This new mystery is irresistible, but Emily and James can't ignore the signs that Mr. Quisling might be the arsonist. The clock is ticking as the fires multiply, and Emily and James race to crack the code of a lifetime.